Pengaruh Komitmen Kuat, Kerja Keras, dan Etika Kerja terhadap Kinerja Pelaku Bisnis di Tempat Wisata Belanja Pasar Cipadu, Kota Tangerang, Provinsi Banten - Herienda, Florensia; Enggriani, Mimi; Mayasari, Ira; Sugeng, Novita Widyastuti; Gantina, Devita (Jurnal Ilmiah Pariwisata, 2024)
This research aims to determine the influence of strong commitment, hard work and work ethic on entrepreneurial performance. This type of research is quantitative descriptive research with multiple regression analysis methods. The location of this research was carried out at the shopping tourist destination at Cipadu Market. The sampling technique uses Accidental Sampling. Partial research results show that strong commitment, hard work and work ethic have a significant influence on the performance of Cipadu Market entrepreneurs. The strong work commitment of business actors at Cipadu Market increases motivation, seriousness and better service to customers as well as resilience to business challenges. The Cipadu market is very competitive, requiring business actors to work hard to differentiate themselves from competitors, keep up with fast-changing fashion trends, and maintain consistent product quality. The high work ethic of business actors at Cipadu Market creates customer trust, builds a positive reputation, and reduces legal risks, all of which contribute to improving business performance. Keywords: strong commitment, hard work, work ethics, performance